THE EFFECTS OF ION IDENTITY AND IONIC STRENGTH ON THE DISSOLUTION RATE OF A GIBBSITIC BAUXITE - Mogollon J.L.; Perez-Diaz A.; Lo Monaco S. (My University, 2000)
The influence of cation and anion identity and concentration, on the far from equilibrium dissolution rate of gibbsite, was studied at 298°K. Input solutions, with initial pH = 3.5 and variable salt type and concentration, were flowed at different rates, through columns packed with a unconsolidated gibbsitic bauxite from Los Pijiguaos-Venezuela ore deposit.It was observed cations Na+, K+, Mg2+ and Ca2+ have no influence on the far from equilibrium dissolution rate. Anions have two different effects: concentration increases of monovalent anions (Cl-, NO3- and ClO4-) causes a decrease in the rate, as a function of [anion](-0.11 +/- 0.01); and increases of sulfate concentration causes an increase in the rate as a function of [SO4=](0.4 +/- 0.1). According to our calculations, these two effects have a remarkable influence upon the lifetime of gibbsite under weathering conditions. Based on Transition State Theory, it is proposed the experimental observations are due to an electrostatic effect on the activated complex (AC#) of the gibbsite dissolution reaction. For this AC# the product of the charge of the involved chemical entities is negative. When SO4= participates in the AC# the product of the charges switches to positive and therefore, the electrostatic interaction increase the dissolution rate.The dissolution rates are independent of the solution saturation degree below ΔGr = - 0.74 kcal/mol. It is inferred that the critical ΔGr is a constant of the solid, not affected by the solution characteristics, e.g., pH, ionic strength, cation and anion identities.